Toward a Framework for Designing Person‐Centered Mental Health Interiors for Veterans. Issue 2 (7th February 2017) - Platt, Lisa Sundahl; Bosch, Sheila J.; Kim, Daejin
ABSTRACT: The Veteran's Administration (VA), recognizing the potential influence that nurturing interior environments may have on patient well‐being, has been designing and constructing mental health settings intended to calm, restore, and revive. Unfortunately, limited research investigates the links between the interior environment and mental health outcomes that can be used for guiding the design for these facilities. This paper seeks to provide a framework for designing person‐centered mental health interiors that would be supportive of human factors for a healthcare organization's clinical and operational staff as well as Veterans. The framework is intended to assist healthcare providers in achieving mental health aims through thoughtful, evidence‐based, person‐centered design. Based on a review of the literature and case study investigations of three VA acute inpatient mental health units in the United States, the framework is comprised of six domains: Involve, Protect, Engage, Comfort, Personalize, and Sustain. These domains, informed by existing credible research and best practices, were vetted through post‐hoc analysis of qualitative data gathered from interviews, focus groups, and/or listening sessions conducted with the three sites. The resultant Framework for Designing Person‐Centered Mental Health Interiors for Veterans, developed based on the data and methodologies used in conducting this study, is meant as a complementary resource for informing future research, planning, design, and operation of acute inpatient mental health spaces. The research team's aim was to develop an accessible set of evidence‐based environmental planning considerations to aid in the prioritization and development of person‐centered mental health environments.